Evaluation of mechanical and optical behavior of current esthetic dental restorative CAD/CAM composites. (March 2015) - Stawarczyk, Bogna; Liebermann, Anja; Eichberger, Marlis; Güth, Jan-Frederik
Abstract: Objectives: To determine the mechanical and optical properties of CAD/CAM composites (LAVA Ultimate, Cerasmart, Shofu Block and two exp. CAD/CAM composites), a hybrid material (VITA Enamic), a leucite (IPS Empress CAD) and a lithium disilicate glass-ceramic (IPS e.max CAD). Materials and methods: Three-point flexural strength (FS) was investigated accordingISO 6872:2008 ( N =240/ n =30). Two-body wear (TBW) was analyzed in a chewing simulator (1, 200, 000 cycles, 50 N, 5°/55 °C) using human teeth as antagonists ( N =120/ n =15). Quantitative analysis of wear was carried out with a 3D-scanner and associated matching software. Discoloration rate (DR) after 14 days of storage in cress, curry, red wine, and distilled water ( N =384/ n =12), and translucency (T) ( N =384/ n =48) of CAD/CAM materials were measured in a spectrophotometer (400–700 nm wavelength). Data were analyzed using two-/one-way ANOVA with Scheffé post-hoc test, Kruskal–Wallis-H test, and linear mixed models ( α =0.05). Results: IPS e.max CAD showed the highest FS ( p <0.001), followed by LAVA Ultimate; however, not different from the remaining CAD/CAM composites (exception: Shofu Block). The lowest FS showed VITA Enamic and IPS Empress CAD ( p <0.001). IPS Empress CAD, VITA Enamic, exp. CAD/CAM composite 2, followed by IPS e.max presented lower material TBW than the remaining CAD/CAM materials ( p <0.001). The highest antagonist wear was observed for the tested glass-ceramics and the hybrid material ( p <0.001). Storage medium (red wine>curry>cress>distilled water) exerted the highest influence on DR ( p <0.001), closely followed by CAD/CAM material. Glass-ceramics showed lower DR than CAD/CAM composites ( p <0.001). Conclusions: CAD/CAM composites presented moderate FS, high T and antagonist friendly behavior. Glass-ceramic demonstrated the most favorable DR and lowest TBW on the material side.